neurology-neurorehabilitation 2017
DOI: 10.35841/neurology-neurorehabilitation.2.1.14-20
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Clerodendron glandulosum against acute transient ischemia reperfusion cerebral injury in rats.

Abstract: C. glandulosum extract) on antioxidant status in I/R (ischemia-reperfusion) injury in the rat forebrain have been investigated. Further, its effect was assessed on behavioural parameters, infract size and histopathological parameters. Bilateral carotid artery occlusion followed by reperfusion produced significant cerebral infarction and impaired short term memory, motor co-ordination and lateral push response CGE markedly attenuated I/R induced cerebral injury in terms of decreased infarct, size. The result su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The neurobehavioral impairment which followed I/R injury in the present study corroborates earlier reports (Gulati & Singh, 2014; Schimidt et al., 2014; Singh & Chopra, 2013; Surapaneni, T, Ansari, & Goli, 2017). Improvement of the behavioral impairment by pretreatment with Trévo™ indicates its ability to attenuate damaging cascades leading to the neurobehavioral dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…The neurobehavioral impairment which followed I/R injury in the present study corroborates earlier reports (Gulati & Singh, 2014; Schimidt et al., 2014; Singh & Chopra, 2013; Surapaneni, T, Ansari, & Goli, 2017). Improvement of the behavioral impairment by pretreatment with Trévo™ indicates its ability to attenuate damaging cascades leading to the neurobehavioral dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…Stroke model of GCIRI used for the cerebrovascular ischemic condition, grey and white matter damage, loss of sensorimotor function, neurobehavioral dysfunction, optical fiber injury, diminished speech, anxiety and loss of memory 50,51,52 . It is well recorded that cerebral ischemia responsible for the impairment in sensorimotor performance and neurobehavioral function 53,54 . We used hanging wire test and rotarod test in the present study to evaluate the effect of GCIRI on sensorimotor performance.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the protective effect of C. glandulosum hydroalcoholic extract on IRI in rat forebrain was reported that showed a significant decrease in infarct size and restored antioxidant enzyme (SOD and Catalase) oxidative defense [117] …”
Section: Pharmacological Aactivitiesmentioning
confidence: 96%
“…[116] In another study, the protective effect of C. glandulosum hydroalcoholic extract on IRI in rat forebrain was reported that showed a significant decrease in infarct size and restored antioxidant enzyme (SOD and Catalase) oxidative defense. [117] From the reported studies, it can be inferred that C. glandulosum extract rendered a cerebroprotective effect and was influential in lowering ischaemic OS and injury by enhancing the antioxidant levels. Certain phytoconstituents reported in C. glandulosum viz., compounds 4, 5, 8, 9, 10, maslinic acid, and stigmasterol possess neuroprotective activities.…”
Section: Effect On the Central Nervous Systemmentioning
confidence: 99%